2021
DOI: 10.1016/j.jaci.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic pulmonary vasculitis as a manifestation of the hyperinflammatory phase of COVID-19

Abstract: Eosinophilic pulmonary vasculitis as a manifestation of the hyperinflammatory phase of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“… 10 , 11 , 12 Presentation may be extremely variable and, in cases of lung involvement, the differential diagnosis between idiopathic vasculitis and COVID‐19 may be challenging. 8 , 9 On the other hand, there have not yet been any reports of cases of patients whose rheumatic condition has worsened or even relapsed after vaccination against COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 12 Presentation may be extremely variable and, in cases of lung involvement, the differential diagnosis between idiopathic vasculitis and COVID‐19 may be challenging. 8 , 9 On the other hand, there have not yet been any reports of cases of patients whose rheumatic condition has worsened or even relapsed after vaccination against COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent post-mortem series of COVID-19 patients, eosinophils were found in the alveolar septs, 62 and several case reports of COVID-19 patients undergoing bronchoalveolar lavage and/or lung biopsy showed significant eosinophilic infiltrates in lungs. 63,64 Taken together, all these observations may provide an additional hypothesis explaining why the use of both omalizumab and anti-Th2 cytokines therapies could further improve the clinical course of COVID-19.…”
Section: Impact Of Anti-th2 Therapy On Covid-19: Potential Mechanismsmentioning
confidence: 90%
“…Several isolated incidents of eosinophil-associated complications of COVID-19 have been reported in the literature. Among these cases, Luecke et al [ 105 ] documented a case of isolated pulmonary eosinophilic vasculitis in an older male patient undergoing mechanical ventilation for severe COVID-19. Similarly, Murao et al [ 106 ] reported a case of acute eosinophilic pneumonia triggered by COVID-19 that responded to treatment with prednisolone.…”
Section: Covid-19 In Patients With Eosinophil-associated Diseases Andmentioning
confidence: 99%